The University Student’s Motivation Level on Learning English - Mehdiyev, Esmira; Celal Teyyar Uğurlu; Gonca Usta (European Journal of Social Science Education and Research, 2017)
This study aims to determine the university students’ level of motivation in terms of different variables. A study group of this research has been designed through one of the non-random sampling methods, Using appropriate sampling, 606 students from Faculty of Education of C.U. have been involved in this study. Motivation scale in English Language Learning developed by Mehdiyev,Usta,U?urlu (2015) was used as an instrument of data collection. T-test and one - way analysis of variance (ANOVA) were used to resolve problems of this research. As a result of the research the motivation level of university students hasn’t been revealed significantly different regarding to the gender variable. However, considering the t-test results of motivation scale dimensions, confidence, attitude and personal use, significant difference is seen in favour of women in personal use dimension. The level of language learning motivation of female students is higher than men’s regarding to personal use dimension. However, men’s and women’s views don’t differ significantly in attitude and confidence dimensions. University students don’t present significant differences in terms of birth place, parent’s education level, total motivation scores and confident, attitude and personal dimensions. Students’ motivation levels are seen not to be influenced by the places such as village, provision or city where they have spent the most of their lifetime. At the same time the findings revealed that parental status variable in terms of primary, secondary and university graduates has no effects on students’ motivation.
Keywords: Language Learning, Motivation Scale, Level of Motivation